CMV IgG in the blood is not associated with hepatitis but correlates with poor outcomes in immunotherapy treated melanoma patients - Strobel, Sophia; Machiraju, Devayani; Wiecken, Melanie; Richter, Jasmin; Klein, Julian; Berger, Annemarie; Hassel, Jessica C. (Cancer immunology immunotherapy, 2025)
Cytomegalovirus (CMV) infection or reactivation in immune-compromised individuals can lead to a wide range of severe complications including hepatitis. However, its relation with immune checkpoint inhibitors (ICIs) induced hepatitis (ICI-hepatitis) and tumor responses in advanced melanoma patients remains unclear. Hundred and ninety metastatic cutaneous melanoma patients (mCM) who received ICI treatment, with CMV IgG or IgM information available at baseline, were included in the study (Cohort 1). Clinical characteristics and immune cell count in the blood were retrieved from medical records. In addition, anti-CMV IgG and IgM were measured in pre and on-treatment serum samples from 49 advanced skin cancer patients using ELISA (Cohort 2). In the event of a positive anti-CMV IgM, further analysis with PCR was performed. Univariate and multivariate analysis was used to assess the relationship between CMV IgG or IgM and ICI-hepatitis tumor outcomes. Twenty-one patients (11%) developed hepatitis during ICI treatment (Cohort 1). ICI-hepatitis was significantly associated with disease control rate (DCR; p = 0.017) and longer progression-free survival (PFS; p = 0.008) in mCM patients. Detection of CMV IgG or IgM antibodies were not associated with ICI-hepatitis (p > 0.05). However, increased CMV IgG values at baseline correlated with disease progression (p = 0.047) and shorter PFS (p = 0.081). In addition, increased CMV IgG values were associated with reduced levels of monocytes (p = 0.005), eosinophils (p = 0.062), and neutrophils (p = 0.065) in the blood. In summary, anti-CMV IgG or IgM in the blood may not be associated with ICI-hepatitis, but high anti-CMV IgG at baseline indicates poor outcomes in ICI-treated mCM patients.